Vitamin a deficiency causes apoptosis in the mammary gland of rats - Vasquez Gomez, Miriam Ester (2024)
Subchronic dietary vitamin A deficiency (VAD) causes severe abnormalities, including dysfunction of the epithelia of the mammary gland. However, the underlying mechanism of this process is partially known. Therefore, herein, we used a nulliparous-rat experimental model of dietary VAD for a total dieting regime of 3 and 6 months and intervened (refeed) with a vitamin A sufficient (VAS) diet for 0.5 or 1 month before the end of the diet regime and investigated the underlying molecular mechanism of mammary tissue dysfunction. Dietary vitamin A deficiency for 3 and 6 months caused increased inflammatory cell infiltration in the mammary gland parenchyma and glandular cells, with increased inflammation and apoptosis and reduced cell proliferation. These changes can be reversed with a VAS diet. Mammary gland dysfunction after a subchronic VAD is caused by an imbalance between NFκB and retinoic acid-triggered signaling. Inflammation, apoptosis, and impaired proliferation lead to dysfunction of the epithelia of the mammary gland of nulliparous rats fed a VAD diet.